Pollen of colombian magnolias (2016)
The family Magnoliaceae has been of great interest to scientists seeking to understand flowering plant evolution. Morphological characters have been investigated in several studies, especially in China, the country with the highest number of species. Colombia, with 36 species, has the highest number of species in South America. In spite of the family’s evolutionary importance and significant threats to species survival, information is still lacking about Colombian Magnoliaceae due to a paucity of research. In this article, the pollen morphology of fourteen Magnolia species from Colombia is described based on size, shape, apertures, exine and sculpture. Pollen grains from fresh material and herbaria collections were processed using standard acetolysis methods, and morphological descriptions were elaborated based on both light and scanning electron microscopy observations. In this study the pollen grains were considered large (from 68.2 to 115 μm in the longest axis and from 41.4 to 69.3 μm in the shortest axis), boat-shaped and anasulcate. Exine sculpture patterns such as rugulate, psilate, perforate and combinations of these types were found in the species analyzed. Although there is high uniformity in the shape of the pollen grains, some differences were found among species, not only in size but also in ornamentation. The high uniformity of pollen morphology among the Colombian species supports the most recent classification of the American magnolias.Key words.Dugandiodendron, Neotropics, pollen morphology, Talauma